2017
DOI: 10.1016/j.geomorph.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Storms, channel changes, and a sediment budget for an urban-suburban stream, Difficult Run, Virginia, USA

Abstract: Determining erosion and deposition rates in urban-suburban settings and how these processes are affected by large storms is important to understanding geomorphic processes in these landscapes. Sediment yields in the suburban and urban Upper Difficult Run are among the highest ever recorded in the Chesapeake Bay watershed, ranging from 161 to 376 Mg/km 2 /y. Erosion and deposition of streambanks, channel bed, and bars and deposition of floodplains were monitored between 1 March 2010 and 18 January 2013 in Upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 55 publications
2
64
0
Order By: Relevance
“…Since fine sediments (silt and clay) are particularly susceptible to effects of freeze thaw (Couper 2003;Wynn and Mostaghimi 2006), fine-grained millpond legacy sediments along the streambanks, as in case of our study sites, would especially be vulnerable to this erosion. Large contributions of streambank sediments to suspended sediment exports have previously been reported for Piedmont watersheds (Gellis et al , 2017Voli et al 2013). Gellis et al (2017) reported that eroding streambanks accounted for as much as 70% of the suspended sediment fluvial exports from tropical storms Lee and Sandy.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Since fine sediments (silt and clay) are particularly susceptible to effects of freeze thaw (Couper 2003;Wynn and Mostaghimi 2006), fine-grained millpond legacy sediments along the streambanks, as in case of our study sites, would especially be vulnerable to this erosion. Large contributions of streambank sediments to suspended sediment exports have previously been reported for Piedmont watersheds (Gellis et al , 2017Voli et al 2013). Gellis et al (2017) reported that eroding streambanks accounted for as much as 70% of the suspended sediment fluvial exports from tropical storms Lee and Sandy.…”
Section: Discussionmentioning
confidence: 88%
“…Freeze-thaw cycles cause bank sediments to lose their cohesive strength with subsequent detachment and slumping/collapse at the base of the streambank (Merritts et al 2013;Wolman 1959;Wynn 2006). Freeze-thaw erosion (Couper 2003;Lawler 1993a, b;Merritts et al 2011Merritts et al , 2013Wolman 1959) along with fluvial erosion with large storms (Gellis et al 2017) and mass wasting of stream banks (Fox et al 2016) have been hypothesized as some of the important mechanisms for erosion of stream-bank sediments. Wynn and Mostaghimi (2006) have also shown that the number of freeze-thaw cycles has a cumulative destabilizing effect on streambank sediments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations